2013
DOI: 10.1073/pnas.1304410110
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific regulation of natural killer cell homeostasis and response against viral infection by microRNA-155

Abstract: Natural killer (NK) cells function in the recognition and destruction of host cells infected with pathogens. Many regulatory mechanisms govern the potent responses of NK cells, both at the cellular and molecular level. Ablation of microRNA (miRNA) processing enzymes demonstrated that miRNAs play critical roles in NK cell differentiation and function; however, the role of individual miRNAs requires further investigation. Using mice containing a targeted deletion of microRNA-155 (miR-155), we observed defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
112
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 42 publications
3
112
0
1
Order By: Relevance
“…Using ZBTB32-deficient mice, it was demonstrated that ZBTB32 facilitated proliferation by counteracting the anti-proliferative factor BLIMP1 (also known as PRDM1) 57 . In addition, NK cells lacking the microRNA miR-155 exhibited severely reduced effector and memory cell numbers after MCMV infection 58 . Although the genes encoding the known receptors expressed by NK cells do not require rearrangement, NK cells lacking RAG showed impaired expansion and persistence after MCMV infection, suggesting an important role for RAG in the optimal generation of MCMV-specific memory NK cells 59 .…”
Section: Box 2 | Regulation Of Nk Cells By Activating and Inhibitory mentioning
confidence: 99%
“…Using ZBTB32-deficient mice, it was demonstrated that ZBTB32 facilitated proliferation by counteracting the anti-proliferative factor BLIMP1 (also known as PRDM1) 57 . In addition, NK cells lacking the microRNA miR-155 exhibited severely reduced effector and memory cell numbers after MCMV infection 58 . Although the genes encoding the known receptors expressed by NK cells do not require rearrangement, NK cells lacking RAG showed impaired expansion and persistence after MCMV infection, suggesting an important role for RAG in the optimal generation of MCMV-specific memory NK cells 59 .…”
Section: Box 2 | Regulation Of Nk Cells By Activating and Inhibitory mentioning
confidence: 99%
“…Furthermore, the differentiation defect observed in miR15a/16-1 is phenocopied by cMyb overexpression and partially corrected upon cMyb knockdown [33]. In contrast, an increase in mature "NK-cell" numbers was reported in miR-155 −/− mice, but the relevant targets were not identified [34]. This underlines the pleiotropic role of microRNAs and suggests that more microRNA-target mRNA interactions are still to be discovered.…”
Section: Discussionmentioning
confidence: 60%
“…Suppressors of cytokine signaling 1 (SOCS1) negatively regulates this pathway. In addition, it is also a well-acknowledged miR-155 target in immune cells [34,37]. Indeed, miR-155Tg NK cells present an increased response to IL-2 [38] and miR-155 −/− Treg a defective one [39].…”
Section: Discussionmentioning
confidence: 99%
“…Hirofumi et al postulated that miR-141 was a potential metastasis inhibitor in renal cancer and reported that upregulation of miR-141 inhibited migration of cancer cells. They demonstrated that miR-141 induced dysregulation of genes related to migration and invasion, including ZEB1 [17]. It was indicated that miR-141 was likely to have a number of targets through which it regulated biological functions on cancer cells.…”
Section: Discussionmentioning
confidence: 99%